Pengaruh perawatan luka teknik modern dressing terhadap penyembuhan luka post operasi section caesarea - Kalvin Ginting; Basri Basri; Arlis Arlis (STIKes Surya Global Yogyakarta, 2023)
Inappropriate postoperative wound care measures often inhibit the wound healing process including the use of NaCl gauze compresses as an effort to maintain moisture can not be maintained longer so that the wound must be replaced more often, this phenomenon will have an impact on the re-injury of the wound bed which will stimulate re-inflammation of the wound bed. The use of antiseptics, such as 1% iodine and H2O2 in conventional treatments can trigger damage to blood capillaries, this will affect the stress conditions of tissues that are regenerating. The purpose of this study was to assess the condition of postoperative sectio caesarea wounds before modern wound dressing techniques were applied. The experimental design in this study used pre-experimental using one group pretest-posttest design. From the results of modern wound dressing treatment, the majority of the basic color of the wound was pink as many as 12 people (80%), the type of exudate did not exist as many as 15 people (100%), the amount of exudate was minimal as many as 15 people (100%), and the surrounding skin was healthy as many as 15 people (100%). After being analyzed, the resulting p value is 0.000 so it can be concluded that there is an effect of modern dressing technique wound care on postoperative sectio caesarea wound healing.